Emotional Intelligence in Managerial Economic Decision-Making - Aida, Iqlillah Nur; Muhammad, Faishal; Anjani, Andi Dwi (Universitas Sains dan Teknologi Komputer, 2025)
In today’s complex organizational environment, Emotional Intelligence (EI) plays a critical role in shaping the quality of economic decision-making by managers. This study investigates how the dimensions of EI—namely self-awareness, emotional regulation, and empathy—influence strategic decision processes across various industries. Using a descriptive qualitative approach with thematic analysis, data were gathered from semi-structured interviews with 10 senior managers, supported by observations and organizational documents. The findings reveal that EI serves as an internal mechanism that stabilizes cognitive processes under organizational pressure, reduces decision bias, and enhances the social legitimacy of economic decisions. The integration of EI fosters a balance between rational analysis and affective insight, leading to more ethical and adaptive decisions. This study offers an integrative model connecting EI dimensions with key stages of economic decision-making and provides practical implications for managerial training and organizational policy. It advocates for interdisciplinary approaches to better understand emotionally-informed economic behavior.